2021
DOI: 10.3390/ijms221810041
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and NADPH Oxidase: Connecting Electromagnetic Fields, Cation Channels and Biological Effects

Abstract: Electromagnetic fields (EMFs) disrupt the electrochemical balance of biological membranes, thereby causing abnormal cation movement and deterioration of the function of membrane voltage-gated ion channels. These can trigger an increase of oxidative stress (OS) and the impairment of all cellular functions, including DNA damage and subsequent carcinogenesis. In this review we focus on the main mechanisms of OS generation by EMF-sensitized NADPH oxidase (NOX), the involved OS biochemistry, and the associated key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 86 publications
2
7
0
Order By: Relevance
“…In accordance with the tenor of the present review article, several authors have proposed voltage-gated (dependent) ion channels as molecular transducers of weak external EMF fields into biological signals (e.g., Pall, 2013Pall, , 2015Pall, , 2016Li et al, 2020a;Georgiou and Margaritis, 2021;Panagopoulos et al, 2021;Wust et al, 2021). Identification of voltage-gated ion channels as central functional units in electrolocation of fishes (see section 4 "Biological voltmeters" of this article) may further support this "ion channel hypothesis" of external EMF perception.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with the tenor of the present review article, several authors have proposed voltage-gated (dependent) ion channels as molecular transducers of weak external EMF fields into biological signals (e.g., Pall, 2013Pall, , 2015Pall, , 2016Li et al, 2020a;Georgiou and Margaritis, 2021;Panagopoulos et al, 2021;Wust et al, 2021). Identification of voltage-gated ion channels as central functional units in electrolocation of fishes (see section 4 "Biological voltmeters" of this article) may further support this "ion channel hypothesis" of external EMF perception.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that NADPH Oxidases (NOXs) can promote ROS accumulation in cells and exacerbate inflammatory responses in certain mammalian cells, by promoting the activation of inflammatory pathways and the production of inflammatory factors [ 31 , 32 ]. Antioxidant enzymes, including SOD, SOD2, and peroxidases such as GPX and CAT, play a crucial role in antioxidant defense by regulating ROS levels [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mitochondrial electron transport chain, ROS can also be generated through the catalytic reaction of NADPH oxidase (NOX) [ 20 ]. NOX plays a crucial role in the production of ROS by reducing O 2 to H 2 O 2 through the donation of a second electron to O 2 · − [ 1 , 21 ]. H 2 O 2 , serving as a messenger molecule, assumes a pivotal role in redox sensing, signaling, and redox regulation, with its production primarily stemming from the breakdown of O 2 through a swift and efficient reaction [ 22 ].…”
Section: Os and Rosmentioning
confidence: 99%